2022
DOI: 10.3390/molecules27144657
|View full text |Cite
|
Sign up to set email alerts
|

Physiology-Based Pharmacokinetic Study on 18β-Glycyrrhetic Acid Mono-Glucuronide (GAMG) Prior to Glycyrrhizin in Rats

Abstract: To understand that 18β-Glycyrrhetic acid 3-O-mono-β-D-glucuronide (GAMG) showed better pharmacological activity and drug-like properties than 18β-Glycyrrhizin (GL); a rapid and sensitive HPLC-MS/MS method was established for the simultaneous determination of GAMG and its metabolite 18β-Glycyrrhetinic acid (GA) in rat plasma and tissues after oral administration of GAMG or GL. This analytical method was validated by linearity, LLOQ, specificity, recovery rate, matrix effect, etc. After oral administration, GAMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that GA-specific receptors are expressed on hepatocytes (Stecanella et al 2021), which may be related to the fast accumulation of GA in the livers. However, it is not clear whether GA’s accumulation in other organs, including the lung 51 and the colon, 52 is associated with the GA-receptors. Whether the distribution of free TAN in various tissues is related to its physicochemical properties and receptors has not been reported so far, which needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that GA-specific receptors are expressed on hepatocytes (Stecanella et al 2021), which may be related to the fast accumulation of GA in the livers. However, it is not clear whether GA’s accumulation in other organs, including the lung 51 and the colon, 52 is associated with the GA-receptors. Whether the distribution of free TAN in various tissues is related to its physicochemical properties and receptors has not been reported so far, which needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…Physiology-based pharmacokinetic studies indicated that GAMG can be absorbed quickly and effectively, and exert better pharmacological activities than GL. GAMG exhibited benign drug-like properties due to higher blood concentration and higher tissue distribution in the lungs and kidney [ 153 ]. GAMG can inhibit COVID-19 virus and remedy COVID-19 associated pneumonia.…”
Section: Prospective Viewmentioning
confidence: 99%
“…After entering the blood, glycyrrhizic acid undergoes hydroxylation or GluA (+GluA) and is catalysed by metabolic enzymes such as liver cytochrome P450 isoenzyme (cytochrome P450 isoenzyme, CYP450s) and UDP‐GluA transferase (UDP‐glucuronyl transferases, UGTs) to generate the corresponding metabolites (Koyama et al, 2017; W. Song et al, 2018). The main metabolites are glycyrrhetinic acid and 18β‐Glycyrrhetic acid 3‐O‐mono‐β‐ d ‐glucuronide (M. Cao et al, 2022). Moreover, Liquiritin can be deoxidized glucose (Glc) into liquiritigenin by digestive tract microorganisms, and then be absorbed into blood (S. Dong et al, 2014).…”
Section: Absorption Distribution Metabolism and Excretion (Adme) Of G...mentioning
confidence: 99%